Optimizing the electromagnetic wave absorption performance of designed hollow CoFe2O4/CoFe@C microspheres. (10th August 2021) - Ge, Jianwen; Liu, Shimeng; Liu, Li; Cui, Yu; Meng, Fandi; Li, Yixing; Zhang, Xuefeng; Wang, Fuhui
Graphical abstract: Highlights: Hollow structures with certain polarity characteristics were synthesized. Oxygen vacancies and high Ms can be formed by carbon reduction. The EAB is of 5.9 GHz at 2.17 mm and the RLmin is up to -51 dB with 30 wt% loading. Abstract: Whereas hollow composites present some superiorities like abundant micro interfaces, outstanding impedance matching as the responses of electromagnetic wave (EMW), but versatile designs including crystal transformation, heterogeneous structures and magnetic exchange coupling to further contribution are even not designed or stressed together in previous literatures. In this article, rational design on the hollow CoFe2 O4 /CoFe@C architecture has been conducted by a sequential process of self-sacrifice by combustion, in-suit polymerization and calcination. Results of morphology observation exhibit that heterogeneous CoFe2 O4 /CoFe@C composites were generated via crystal transformation from CoFe2 O4 to CoFe alloys with encapsulated carbon, together with ultimate growth of crystal particles. As for three carbon-based architectures, relatively low-graphitization carbon layers are favorable for enhancing impedance matching and polarization relaxation, but suppressing the conductive loss essentially. Moderate carbon content endows sample S2 with the maximum magnetic saturation ( M s ) of 152.4 emu g −1 . The optimized RL of sample S3 is up to -51 dB with 30 wt% loading, and the effective absorption band (EAB) is of 5.9 GHz at the thickness of 2.17 mm, while 6.0 GHz can be reached at 2.5 mm. Therefore, this hollow multi-interfaces design definitely shed light on novel structure for new excellent absorbers.